2019
DOI: 10.1016/j.tafmec.2019.102269
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural damage mechanics-based model for creep fracture of 9%Cr steel under prior fatigue loading

Abstract: Predicting the remnant creep fracture life precisely is crucial for ensuring safety of high temperature components. This study presents a microstructural damage mechanics-based model for creep fracture of 9%Cr steel under prior fatigue loading. Microstructure observation reveals that the decrease of dislocation density and the growth of martensite lath width occurred during prior fatigue process contribute to the degradation of creep strength. Particularly, coarsening of martensite lath width plays the dominat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Besides the loading mode, the exertion of duration period also influenced the creep‐fatigue performance. The effect of prior CFI damages and prior fatigue damage on remaining tensile and creep properties of 9%Cr steel was studied by Zhang et al 30,31 and revealed the prior performance could significantly reduce tensile strength and creep resistance. When studying the performance of alloy 709, Porter et al 32 and Amrita et al 25 also found that creep‐fatigue life was reduced in comparison with low cycle fatigue life at different temperatures, and more life reduction was observed at low temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the loading mode, the exertion of duration period also influenced the creep‐fatigue performance. The effect of prior CFI damages and prior fatigue damage on remaining tensile and creep properties of 9%Cr steel was studied by Zhang et al 30,31 and revealed the prior performance could significantly reduce tensile strength and creep resistance. When studying the performance of alloy 709, Porter et al 32 and Amrita et al 25 also found that creep‐fatigue life was reduced in comparison with low cycle fatigue life at different temperatures, and more life reduction was observed at low temperature.…”
Section: Introductionmentioning
confidence: 99%